Índices de difusión generalizados de la actividad económica estatal y sectorial para México - Santiago Guerrero Escobar; Juan Carlos Martínez-Ovando (Banco de México, 2014)
– In this research we develop generalized diffusion indexes for the Mexican state and sectorial economic activity. These indexes summarize the dynamics of the local cycles in a way that they are consistent with the aggregate economic activity. The proposed index includes three dimensions of the local dynamic activity: i) the variation of local cycles (positive or negative), ii) the magnitude of these variations and iii) the weight of local components (states and/or sectors) on the aggregate economic activity. The main contribution of these indexes is that they admit sub-aggregations of regions and/or sectors that are more precise and informative than their counterparts. We show two applications. In the first one, we develop the generalized diffusion index for the Mexican economy using state economic coincident indexes. In the second one, we create a diffusion index of the state and sectorial economic activity using the State Quarterly Indicator of Economic Activity (ITAEE by its Spanish acronym) produced by INEGI.
Keywords: C1; C5; E3; 330; Diffusion index; Coincident indexes; Economic cycles; Monitoring